INCLUSIVE GROWTH IN INDIA : AGRICULTURE,POVERTY,AND HUMAN DEVELOPMENT - S MAHENDRA DEV (NEW DELHI OXFORD UNIVERSITY PRESS, 2007)
This volume emphasizes the need for economic reforms with equitable development. It examines the performance, issues, challenges, and policies in inter-related elements of inclusive growth: agriculture, poverty reduction, human development, food security, social sector, and regional disparities.
Keywords: ECONOMIC DEVELOPMENT-INDIA; ECONOMIC POLICY-INDIA